Abnormal levels of apolipoprotein A-I in chronic thromboembolic pulmonary hypertension. (April 2021) - Khirfan, Ghaleb; Li, Manshi; Wang, Xiaofeng; DiDonato, Joseph A.; Dweik, Raed A.; Heresi, Gustavo A.
Recent studies have shown low high-density lipoprotein cholesterol (HDL-C) and dysregulated lipid metabolism in chronic thromboembolic pulmonary hypertension (CTEPH). Apolipoprotein A-I (ApoA-I) is the major protein component of HDL-C and mediates most of its functions. We hypothesize that ApoA-1 and its oxidative state might be more sensitive biomarkers in CTEPH. Plasma levels of HDL-C, ApoA-I, paraoxonase-1 enzyme activity (PON1), and the oxidized dysfunctional ApoA-I (oxTrp72-ApoA-I) were measured in patients with CTEPH and compared to those in healthy controls. Association with markers of disease severity in CTEPH was assessed. We included a total of 61 patients with CTEPH (age: 61.2 ± 15 years; male 52.5%) and 28 control subjects (age: 60.1 ± 8 years; male 59.3%). When adjusting for age, sex, body mass index, and statin use, ApoA-I was lower in CTEPH compared to controls (CTEPH:125.2 ± 27 mg/dl; control:158.3 ± 29.4 mg/dl; p < 0.001), but HDL-C levels were not statistically different. There were no significant differences in PON and oxTrp72-ApoA-I/ApoA-I ratio. In exploratory analyses, ApoA-I was associated with mean right atrial pressure (rs = −0.32, p = 0.013) and N-terminal pro B-type natriuretic peptide (rs = −0.31, p = 0.038). There were no significant associations between HDL-C, PON1, or oxTrp72-ApoA-I/ApoA-I ratio and markers of disease severity. We conclude that ApoA-I is a more sensitive biomarker than HDL-C in CTEPH, and may be associated with right heart dysfunction.